The 'umran al 'alam theory's approach to the social smart city ethical - Adnan, Siti Nur Najiah; Awang, Jaffary; Rahman, Zaizul Ab; Ibrahim, Mazlan; Long, Ahmad Sunawari; Kamarzaman, Mohd Haidhar; Yusof, Muhammed; Mohamed, Shahrulanuar (IAEME Publication, 2018)
Ibn Khaldun is known as ‘kultur historiker’ which means the historian of civilization. He becomes infamous with his uniqueness and authenticity thought in sociology and anthropology field. These field emphasize on culture, social interaction and study about society itself. Besides, his contributions helps the development of society institutions. He presents ‘umran as an ideology that concludes all the elements of sociology and anthropology. Society is a main subject and focus on ‘umran studies. ‘Umran consists studies of ecology, political, rural and urban society, economic sociology and knowledge sociology. ‘Umran is widely known by intellectuals figures, however it is not familiar among society. Hence, this article is an introduction in understanding umran and it’s significant in society.